Human–Structure System Coupled Vibration Test and Human Body Model - Xiaotong Chen; Yaofa Lin; Mao Ye; Liqin Wu (Buildings)
Most studies on human–structure interactions have focused on vertical coupling, which refers to the interaction between human bodies and structures in the vertical direction. This study, however, analyzes horizontal coupling. Several experiments on mass–structure and human–structure systems were conducted, and two horizontal-coupling human–structure models are proposed. The experimental results indicate that a stationary human body should not be regarded as a simple mass. As the number of individuals increases, the horizontal self-resonance frequency gradually decreases by approximately 0.2–0.3 Hz, whereas the damping ratio increases. Based on experimental data and horizontal human–structure models, the horizontal frequency ranges of the human body are found to be 0.236–3.748 Hz for front–back motion and 0.194–5.32 Hz for left–right motion. It is proposed that the single-human model and experimental results be extended to crowd–structure interactions.